Metabolic Syndrome and Breast Cancer: Prevalence, Treatment Response, and Prognosis - Dong, Shuwen; Wang, Zheng; Shen, Kunwei; Chen, Xiaosong (Frontiers in Oncology, 2021)
Metabolic syndrome is a type of multifactorial metabolic disease with the presence of at least three factors including obesity, diabetes mellitus, low high-density lipoprotein, hyper-triglyceridemia, and hypertension. Recent studies have shown that metabolic syndrome and its related components exert a significant impact on the initiation, progression, treatment response, and prognosis of breast cancer. Metabolic abnormality not only increases the disease risk and aggravates tumour progression, but also leads to unfavourable treatment response and more treatment side effects. Moreover, biochemical reactions caused by the imbalance of these metabolic components affect both the host general state and organ-specific tumour microenvironment, resulting in a higher rate of recurrence and mortality. Therefore, this review discusses the recent advances in association of metabolic syndrome and breast cancer, which can provide potential novel therapeutic targets and intervention strategies to improve breast cancer outcome.